Molecular detection of Haemophilus parasuis serotypes 4, 5 or 12 and 13 in Peninsular Malaysia - Lee, Chee Yien; Ooi, Peck Toung; Zakaria, Zunita; Mohamed Mustapha, Noordin (Malaysian Society of Parasitology and Tropical Medicine, 2019)
Although the economic importance of Haemophilus parasuis infection causing Glasser's disease is prevalent throughout pig farms in Peninsular Malaysia, there is a dearth of knowledge on its actual nature. In this study, a multiplex PCR was performed to screen for three major predominant virulent strains of H. parasuis, which are serotypes 4, 5 or 12 and 13. A total of 175 tissues or bodily fluid samples of various parts were collected from diseased animals from October, 2016 to February, 2018; with total of 62.9% positive detection of H. parasuis. The highest detection was found to be in the pericardial sac fibrin (90.9%) followed by pleural fibrin, lung, pleural fluid, tonsil, pericardial sac, peritoneal fluid, abdominal fibrin, joint fluid, brain and pericardium. Serotype 13 was the highest (40/110) followed by serotype 4(37/110), serotype 5(31/110) and 12 samples were nontypable (12/110). The presence of untypable serotype also drives to further identification of other serotypes in Malaysia.